Polar Cousins Comparing Antarctic and Arctic Geostrategic Futures - Leuprecht, Christian; Causey, Douglas (Beyond Boundaries: Canadian Defence and Strategic Studies, 2022)
Geopolitics and climate change now have immediate consequences for national and international security interests across the Arctic and Antarctic. The world's polar regions are contested and strategically central to geopolitical rivalry. At the same time, rapid political, social, and environmental change presents unprecedented challenges for governance, environmental protection, and maritime operations in the regions. With chapters that raise awareness, address challenges, and inform policy options, Polar Cousins reviews the state of strategic thinking and options on Antarctica and the Southern Oceans in light of experience in the circumpolar North. Prioritizing strategic issues, it provides an essential discussion of geostrategic thinking, strategic policy, and strategy development. Featuring contributions from international defence experts, scientists, academics, policymakers, and decisionmakers, Polar Cousins offers key insights into the challenges unique to the polar regions.